PENINGKATAN KADAR HEMOGLOBIN REMAJA PUTRI ANEMIA MELALUI SUPLEMENTASI BUBUR KACANG HIJAU DAN MERAH - Fitriani Unyil, Rani; Fitriani, Rani (Jurnal LENTERA, 2024)
Mung beans and red beans contain vitamin A, calcium, and potassium, which can increase hemoglobin levels in the body. The prevalence of anemia in Indonesia is 23.7%, with the incidence of anemia in females being much higher than in males, at 27.2% in females and 20.3% in males in 2018, showing an increase from 2013 to 2018. Therefore, this community service aims to increase hemoglobin levels in anemic adolescent girls through supplementation with mung bean and red bean porridge. The methods used include nutrition education, training on making bean porridge, and regular health monitoring, with evaluations using questionnaires, structured interviews, and participatory observation. The evaluation results showed a significant increase in hemoglobin levels in all 10 adolescent girls (100%) involved in the program after supplementation, as well as high satisfaction with the materials and the benefits of the information provided. In conclusion, this program is effective in increasing hemoglobin levels and providing beneficial nutrition education for anemic adolescent girls.